The Function of cGAS-STING Pathway in Treatment of Pancreatic Cancer - Mohseni, Ghazal; Li, Juan; Ariston Gabriel, Abakundana Nsenga; Du, Lutao; Wang, Yun-shan; Wang, Chuanxin (Frontiers in Immunology, 2021)
The activation of stimulator of interferon genes (STING) signaling pathway has been suggested to promote the immune responses against malignancy. STING is activated in response to the detection of cytosolic DNA and has the ability to induce type I interferons and link innate immunity with adaptive immune system. Due to accretive evidences demonstrated that STING pathway is involved in regulating immune cells of the tumor microenvironment (TME), STING as a cancer biotherapy has attracted considerable attention. Pancreatic cancer, with a highly immune surveillance TME, still remains a fatal cancer. STING has been applied to the treatment of pancreatic cancer through distinct strategies. This review reveals the role of STING signaling on not only pancreatic tumors but also other disease related to pancreas. We then discuss new advances of STING in either monotherapy or combination methods for the immunotherapy of pancreatic cancer.